2006
DOI: 10.1111/j.1574-6968.1997.tb10447.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of chitin synthase activity in the dimorphic fungus Benjaminiella poitrasii by external osmotic pressure

Abstract: The effects of changes in external osmotic pressure on chitin synthase activity of a dimorphic fungus, Benjaminiella poitrasii, have been investigated. Mycelial and yeast cells incubated in medium of low osmolality (distilled water, 0 mOsm) for 10 min had 2-3-fold higher specific activities of native chitin synthase in mixed membrane preparations than cells that had been subjected to a high osmolality medium (1.2 M sorbitol in distilled water, 1612 mOsm). Cells suspended in media of different osmolalities for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…In our study, we observed a significant decrease of chitin level in the cell wall of T. reesei grown with 1 M sorbitol, even though the total glucan level was more than twice lower than in the control. These results are in agreement with a study on the dimorphic fungus Benjaminiella poitrasii which, when grow in high osmolarity conditions, exhibited a decreased chitin synthase activity (Deshpande et al 1997).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we observed a significant decrease of chitin level in the cell wall of T. reesei grown with 1 M sorbitol, even though the total glucan level was more than twice lower than in the control. These results are in agreement with a study on the dimorphic fungus Benjaminiella poitrasii which, when grow in high osmolarity conditions, exhibited a decreased chitin synthase activity (Deshpande et al 1997).…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, it is well known that in hypo‐osmotic challenged cells, as a consequence of influx of water, cells swell and Mpk1p is transiently activated. In addition, it has also been reported that chitin synthesis is stimulated in cells grown in hypotonic conditions with respect to hypertonic ones (Davenport et al , 1995; Deshpande et al , 1997; Munro et al , 1998; Popolo et al , 1997; Turchini et al , 2000). In addition, it has been recently found that in cells defective in β(1,3)‐glucan synthesis, loss of downregulation of the HOG pathway or deletion of the glycerol channel Fps1p are detrimental for growth (Lesage et al , 2004).…”
Section: Discussionmentioning
confidence: 95%
“…In S. cerevisiae , the HOG pathway is required for the response to CFW and mutants in several components of the pathway are resistant to CFW (Garcia‐Rodriguez et al ., 2000). In addition, changes in osmotic pressure have been shown to regulate chitin synthase activity in the dimorphic fungus Benjaminiella poitrasii suggesting the HOG pathway is involved in chitin regulation (Deshpande et al ., 1997).…”
Section: Introductionmentioning
confidence: 99%